2015
DOI: 10.1177/2047487315599892
|View full text |Cite
|
Sign up to set email alerts
|

Risk of atrial fibrillation in diabetes mellitus: A nationwide cohort study

Abstract: Diabetes increases the risk of developing atrial fibrillation and especially young diabetes patients have a high relative risk. Increased focus on detecting atrial fibrillation in young diabetes patients might prove beneficial, and both anticoagulation treatment and anti-arrhythmic treatment strategies should be considered as soon as possible.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
58
0
5

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 102 publications
(64 citation statements)
references
References 41 publications
1
58
0
5
Order By: Relevance
“…A similar pattern was seen in individuals with type 1 diabetes in a previously published cohort study from Sweden [13]. Additionally, a Danish cohort study reported that the risk of atrial fibrillation in individuals with type 2 diabetes was most pronounced in younger patients [15]. When analyzing the excess risk of atrial fibrillation in relation to renal complications, an increased excess risk of atrial fibrillation was observed with greater albuminuria and eGFR.…”
Section: Discussionsupporting
confidence: 77%
“…A similar pattern was seen in individuals with type 1 diabetes in a previously published cohort study from Sweden [13]. Additionally, a Danish cohort study reported that the risk of atrial fibrillation in individuals with type 2 diabetes was most pronounced in younger patients [15]. When analyzing the excess risk of atrial fibrillation in relation to renal complications, an increased excess risk of atrial fibrillation was observed with greater albuminuria and eGFR.…”
Section: Discussionsupporting
confidence: 77%
“…Figure S12 in Appendix) (28, 40, 50, 79, 88, 95). For renal function, three reports were inverse but non-significant, five reports were direct but non-significant, and three reports showed significant direct associations (see Appendix p 11 and Suppl.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, some antihypertensives, such as β‐blockers and calcium channel blockers, may be protective against AF, and thereby attenuate the association between hypertension and AF. Ideal FBG may also be associated with the reduced risk of AF, perhaps reflecting the contribution of diabetes to AF . Our results indicate that ideal FBG significantly reduces the prevalence of AF but not in individuals over 60 years of age.…”
Section: Discussionmentioning
confidence: 63%
“…Ideal FBG may also be associated with the reduced risk of AF, perhaps reflecting the contribution of diabetes to AF. 31 Our results indicate that ideal FBG significantly reduces the prevalence of AF but not in individuals over 60 years of age. This may be explained by the fact that employees of the oilfield accounted for a large proportion of the population in the present study, and these employees tended to be younger.…”
Section: Factorsmentioning
confidence: 57%